Computer science - theory and applications 6th international computer science symposium in Russia, CSR 2011, St. Petersburg, Russia, June 14-18, 2011. proceedings - Kulikov, Alexander; Vereshchagin, Nikolay (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the 6th International Computer Science Symposium in Russia, CSR 2011, held in St. Petersburg, Russia, in June 2011. The 29 papers presented were carefully reviewed and selected from 76 submissions. The scope of topics of the symposium was quite broad and covered basically all areas of the foundations of theoretical computer science.